2020
DOI: 10.1158/1535-7163.mct-18-1302
|View full text |Cite
|
Sign up to set email alerts
|

Precision Chemoradiotherapy for HER2 Tumors Using Antibody Conjugates of an Auristatin Derivative with Reduced Cell Permeability

Abstract: The most successful therapeutic strategies for locally advanced cancers continue to combine decades-old classical radiosensitizing chemotherapies with radiotherapy. Molecular targeted radiosensitizers offer the potential to improve the therapeutic ratio by increasing tumor-specific kill while minimizing drug delivery and toxicity to surrounding normal tissue. Auristatins are a potent class of anti-tubulins that sensitize cells to ionizing radiation damage and are chemically amenable to antibody conjugation. To… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“… 30 32 Conjugation of MMAF with several antibodies resulted in ADCs with potent anti-tumor activities. 33 36 The free carboxyl group of MMAF also facilitates synthesis of drug-linker conjugates with high potency. 37 Trastuzumab and MMAF were selected as a model targeting antibody and cytotoxic payload for synthesizing the PAR polymer-based ADC.…”
Section: Resultsmentioning
confidence: 99%
“… 30 32 Conjugation of MMAF with several antibodies resulted in ADCs with potent anti-tumor activities. 33 36 The free carboxyl group of MMAF also facilitates synthesis of drug-linker conjugates with high potency. 37 Trastuzumab and MMAF were selected as a model targeting antibody and cytotoxic payload for synthesizing the PAR polymer-based ADC.…”
Section: Resultsmentioning
confidence: 99%
“…As a tubulin-binding molecule, dolastatin exerts its cytotoxic effect through the inhibition of microtubule assembly and tubulin-dependent GTP hydrolysis, leading to cell cycle arrest and apoptosis ( 21 ). MMAF differs from another auristatin derivative, monomethyl auristatin E (MMAE), for a C-terminal modification which is aimed to limit membrane permeability and reduce bystander and off-target toxicity ( 22 ). A phase 1 study (NCT01786135) demonstrated the safety of SGN-CD19A in the clinical setting of R/R B-cell NHL, with 30% of evaluable patients achieving a complete response ( 23 ).…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%
“…F7-ADC consists of F7-Ab conjugated to the antimitotic drug, monomethyl auristatin E (MMAE), by cleavable MC-VC-PABC linkers (Figure 2A). An average of four MMAE molecules were conjugated to cysteine residues in the antibody hinge region, following reduction of disulfides (41,42). For non-invasive F7-ADC tracking, we also conjugated a Cy5 fluorophore to a hinge region disulfide via a non-cleavable maleimide linker.…”
Section: Antibody-drug Conjugate Septuximab Vedotin Binds Fzd7mentioning
confidence: 99%
“…F7-Ab-MMAE drug conjugate was synthesized using methods previously described (41,42). A solution (2 mL, 10.2 mg/mL) of F7-Ab was treated with sodium bicine buffer (200 μL, 1M pH 8.3) and sodium diethylenetriaminepentaacetic acid (20 μL, 100 mM pH 7).…”
mentioning
confidence: 99%